Illite crystallinity index an indicator of physical weathering of the Sediments of the Tista River, Rangpur, Bangladesh - Saha, Sudip; H. M. Selim Reza, A.; Kanti Roy, Mrinal (International Journal of Advanced Geosciences, 2020)
The Tista River is a tributary of the Brahmaputra River. The deposits that exposed along the both banks of the Tista River are characterized mainly by sand, sand laden with gravel and pebble with minor amounts of silt and clay. The X-ray Diffraction (XRD) of the clay sized sediments of the Tista River reveals that illite (and/or mica), chlorite, kaolinite, quartz and feldspar are the principal mineral constituents. The minor to trace amounts of lavendulan, glauconite lepidolite, enstatite, sekaninaite and ferrierite minerals were identified in the investigated area. Illite constitutes 36% of the total minerals of the Tista River basin. The values of the illite crystallinity index varies from 0.228 to 0.345, indicating that the illites are relatively well crystallized and derived from the mechanical weathering of pre-existing rocks. The presence of illite and kaolinite suggests their derivation from the crystalline rocks that contain feldspar and mica, as well as from the pre-existing soils and sedimentary rocks. Glauconite forms in the sediments of continental shelf in the marine environment. The accessory minerals like enstatite, sekanianite and ferrierite are derived from basic igneous rocks. The dissolution of copper arsenate mineral, lavendulan might be a source of arsenic in the sediments of the study area.Â Â